Development of squaraine based G-quadruplex ligands using click chemistry - Xin Zhang (Nature Portfolio, 2017)
Abstract The G-quadruplex (G4) structures of nucleic acids are considered to play an intrinsic role in gene expression. To this end, the development of new G4 ligands has attracted extensive research interests towards potential applications as G4-targeted drugs and molecular probes. To date, the majority of G4 ligands have been composed of an extended planar aromatic scaffold that interacts with the terminal G-tetrad plane via π-π interactions, and various side chains that interact with the sugar-phosphate backbone, loops or grooves of the G4 structures. The side chains act to modulate the affinity and selectivity of the G4 ligands, alongside influencing their biodistribution. Here, we present a click chemistry methodology to generate a series of squaraine-based G4 ligand derivatives based on our previously reported G4 probe (named CSTS) but with varing side chains. We find that importantly these new G4 ligand derivatives retain the G4 selectivity, optical properties and low cytotoxicity of CSTS, but exhibit different binding behaviors to G4 structures, and distinct cellular uptake efficiencies. Indeed, of these new complexes, several exhibit much higher affinity and cellular uptake than CSTS. Overall, this novel, facile and highly effective strategy has significant future potential for the high-throughput screening of G4 ligands or probes targeted towards in vivo applications.